Groundwater quality and associated health risks in flood affected public schools: A case study of district Sanghar, Pakistan / Calidad del agua subterránea y riesgos de salud asociados en las escuelas públicas afectadas por inundaciones: un estudio de caso del distrito Sanghar, Pakistán - Sarfraz, Muhammad; Sultana, Nargis; Tariq, Muhammad Ilyas (Tecnología y ciencias del agua, 2020)
Drinking water quality is of vital importance for the healthy life of a community especially if consumer is a teenager. In order to compare groundwater profile of flooded area (FA) and non-flooded area (NFA) of district Sanghar, 120 water samples from public schools were collected and investigated for physico-chemical parameters, essential metals, trace elements and microbiological indicators. Analysis data revealed that 47% samples in FA were contaminated with faecal coliform bacteria as compared to only 8.3% in NFA. On the other hand, chemical indicators like TDS, Ca, Na, K, SO4, Mg and hardness were higher in FA. Comparison of trace elements content with WHO guidelines revealed that concentration of Fe, As and Zn was higher in 66.7%, 31.7% and 13.3% water samples, respectively in FA whereas content of these elements was also on higher side in 3.3%, 23.3% and 1.7% samples in NFA, respectively. Health risk assessment due to high concentration of Fe, As and Zn showed that As HRI>1, for children in 35 and 23% water samples in FA and NFA, respectively.